Penyelesaian Permasalahan Pengadaan Stok di Toko Grosir Naek Menggunakan Logika Fuzzy dengan Metode Tsukamoto - Juwita Sari; Intan Widya Saputri Nst; Lailan Sofinah Harahap (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2024)
Stock management is an important aspect in the operations of a grocery store. By knowing when to add stock, shop owners can optimize the availability of goods without excess stock. In this research, the fuzzy logic method is applied to determine stock procurement decisions based on sales data and remaining stock. The results of the research show that fuzzy logic can be used to assist in making stock procurement decisions with a fairly high level of accuracy.